2005
DOI: 10.1590/s0100-204x2005000200014
|View full text |Cite
|
Sign up to set email alerts
|

Transmisión del Mal de Río Cuarto virus por ninfas de primer y tercer estadio de Delphacodes kuscheli

Abstract: Resumen -Se comparó la capacidad de ninfas de primer y tercer estadío de Delphacodes kuscheli Fennah (Hemiptera: Delphacidae) para adquirir y posteriormente transmitir el Mal de Río Cuarto virus (MRCV), bajo condiciones controladas. Ninfas I y III avirulíferas se alimentaron separadamente de plantas de trigo infectadas durante 48 horas, para luego ser colocadas en subgrupos de tres individuos sobre plantas de trigo sanas. Se realizaron transmisiones seriales utilizando períodos de inoculación de 24 horas. Ambo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…1). These results are in accordance to previously published work on MRCV experimental transmission by D. kuscheli (Arneodo et al 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1). These results are in accordance to previously published work on MRCV experimental transmission by D. kuscheli (Arneodo et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Under experimental conditions, Ϸ30Ð50% of D. kuscheli planthoppers that feed on a MRCV-infected plant can transmit the virus to wheat after a maximum latency period of 17 d (Arneodo et al 2002). Moreover, it has been demonstrated that when D. kuscheli acquires the virus as a Þrst-instar nymph, the transmission efÞciency is higher than when the acquisition occurs during the third instars (Arneodo et al 2005). However, little is known about the mechanisms underlying MRCV transmission and the causes of the low and variable transmission efÞciency achieved under experimental conditions.…”
mentioning
confidence: 99%
“…Laboratory-reared first instar nymphs were used based on previous experiments [25]. After a 12-day latent period, the insects were recovered and individually tested for infectivity through experimental transmissions to select the viruliferous specimens [25,26].…”
Section: Transmission Assaymentioning
confidence: 99%
“…Generally, the virus is more efficiently acquired by nymphs than by adults. In two similar examples, FDV is transmitted by P. saccharicida only if the virus is acquired by first-instar nymphs, but not older instars or adults, and first-instar nymphs of D. kuscheli transmit MRCV with higher efficiency compared with older instar nymphs (Hutchinson and Francki, 1973;Arneodo et al, 2005).…”
Section: Acquisitionmentioning
confidence: 99%